Predictors of successful same‐day discharge and 1‐year outcomes after left atrial appendage closure. Issue 7 (31st October 2022) - Wass, Sojin Youn; Galo, Jason; Yoon, Sung‐Han; Dallan, Luis A. P.; Mogalapalli, Akhil; Ukaigwe, Anene; Attizani, Guilherme F.; Simon, Daniel I.; Arruda, Mauricio; Filby, Steven J.
Abstract: Background: Same‐day discharge (SDD) following left atrial appendage closure (LAAC) is increasingly common but predictors of successful SDD and 1‐year clinical outcomes have not been described. Objective: The purpose of this study was to explore predictors of successful SDD and report 1‐year outcomes in patients undergoing LAAC with SDD. Methods: A prospective analysis was performed over a 20‐month period of 225 consecutive patients that underwent LAAC in a large, academic hospital. All patients included in the study underwent a SDD protocol. Baseline characteristics and 1‐year outcomes of patients discharged same day of the procedure versus those that required at least one overnight stay were compared. Adverse events, procedural success, and procedure times were evaluated. Results: One hundred and sixty‐one patients (72%) of patients were discharged the same day and 64 patients (28%) required at least an overnight stay (non‐SDD: NSDD). NSDD patients were older and more often female. Procedure time was also longer in the NSDD group than in the SDD (63.4 vs. 55.1 min; p = 0.01). While overall procedural success rates were similar between the SDD and NSDD groups (99.4% vs. 98.4%; p = 0.39), NSDD patients had more complications (9.4% vs. 0%; p = 0.01) and higher number of devices per procedure (1.2 vs. 1.0; p = 0.01) as compared to SDD. At 1 year, there were no significant difference between the SDD and NSDD groups in stroke (1.1% vs. 0%; log‐rank p = 0.44) and all‐cause mortality (3.9% vs. 4.7%; log‐rank p = 0.70). Conclusion: In this single‐center LAAC experience, female sex, older age, and longer procedure duration were associated with higher likelihood for need of overnight stay. At 1‐year follow‐up, there were no significant differences in stroke events and death rates between SDD and NSDD groups.